The Effectiveness of "Kancani": An REBT-Based Web Application on Junior High Students' Subjective Well-Being - Fadia Alyani Kumala; Zahrina Mardhiyah (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Abstract. The high prevalence of mental health issues among Indonesian adolescent students signifies persistently low levels of subjective well-being. Junior high school students tend to engage in negative thinking and experience a decline in positive feelings, contributing to mental health issues, as well as low life satisfaction. To address this, enhancing socio-emotional abilities such as emotion regulation, especially in dealing with irrational thoughts as the root of the problem, becomes crucial. This research aims to evaluate the effectiveness of the "Kancani" web app, which implements Rational-Emotive Behavior Therapy (REBT)-based interventions on the subjective well-being of junior high school adolescents. A quasi-experimental one-group pretest-posttest design was employed with 22 junior high school participants aged 12-15 who received the intervention for 2 weeks. The research instruments used were a 25-item Subjective Well-Being scale measuring positive affect (a = 0.861), negative affect (a = 0.861), and life satisfaction (a = 0.828). Data were tested using the paired samples t-test technique. Data were analyzed using paired samples t-test showed that the Kancani web app, with REBT-based interventions, effectively increased the subjective well-being of junior high school students, particularly in the aspects of positive affect and life satisfaction (p = 0.004 < 0.05), although not significantly in reducing negative affect (p = 0.104 > 0.05). Nevertheless, the improvement in the subjective well-being of students after the intervention is still reflected in the descriptive analysis of the mean differences, indicating an increase in positive affect and life satisfaction, as well as a decrease in negative affect.